El Salvador - Shields, Charles J., 1951-; Henderson, James D., 1942- (Philadelphia : Mason Crest Publishers, 2003)
Presents the geography, history, economy, cities and communities, and people and culture of El Salvador. Includes recipes, related projects, and a chronology.
A small, struggling land -- A history of struggle -- A changing economy -- The most crowded country in Central America -- El Salvador's communities and culture -- Salvadoran festivals -- Recipes -- Glossary -- Project and report ideas -- Chronology -- Further reading/internet resources -- For more information -- Index.
Includes bibliographical references (p. 60) and index.
Mode of access: Internet.
Keywords: El Salvador; El Salvador -- Juvenile literature